(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines women’s issues in the works of Jane Austen from a socio-literary perspective. It analyzes how Austen portrays the social status, economic dependence, educational limitations, and moral constraints imposed on women in nineteenth-century English society. Special attention is given to key novels such as Pride and Prejudice, Sense and Sensibility, Emma, and Persuasion, where female characters struggle to balance personal desires with societal expectations. The study highlights Austen’s critique of patriarchal norms and her contribution to the development of female individuality and gender awareness in literature. The findings demonstrate that Austen’s works remain relevant in understanding the evolution of women’s roles and rights in both historical and modern contexts.